PERLINDUNGAN KONSUMEN PERSPEKTIF HAK-HAK ASASI MANUSIA - Eman Sulaiman (Jurnal Tomalebbi, 2022)
Abstract: This article describes consumer protection from a human rights perspective. The results of the study obtained an understanding that human existence, both as individuals and as social beings, lacks meaning when their human rights are only limited to the expression of rights in the fields of politics and security. Humans need to eat and drink, need to be healthy, have the right to enjoy welfare and other rights in the economic field. All human rights in the field of economy play a decisive role in realizing human integrity as beings who have dignity and worth. The right to the availability of sufficient food and drink, the right to health, the right to product safety and security, the right to economic protection, including the right to compensation and other consumer rights, are rights that are linked to human rights. . Thus, the provision of economic legal instruments in the context of realizing the objectives of economic development is part of the instrument for protecting human rights. Wherever and under any circumstances, consumer rights as an inseparable part of human rights must be respected and upheld. Law No. 8 of 1999 concerning Consumer Protection, must be socialized continuously, not only periodically but continuously. Such efforts should also not only be carried out by the government but should also involve community institutions such as non-governmental organizations and higher education institutions.